Guidance for Canadian Breast Cancer Practice: National Consensus Recommendations for Clinical Staging of Patients Newly Diagnosed with Breast Cancer - Jeffrey Q. Cao; Brae Surgeoner; Mita Manna; Jean-François Boileau; Karen A. Gelmon; Muriel Brackstone; Christine Brezden-Masley; Katarzyna J. Jerzak; Ipshita Prakash; Sandeep Sehdev; Stephanie M. Wong; Nathaniel Bouganim; et al. (Current Oncology)
The accurate staging of breast cancer is fundamental for guiding treatment decisions and predicting patient outcomes. However, there can be considerable variation in routine clinical practice based on individual interpretation of guidelines and depending on the healthcare provider initially involved in working up patients newly diagnosed with breast cancer, ranging from primary care providers, triage nurses, surgeons, and/or oncologists. The optimal approach for clinical staging, particularly in asymptomatic patients presenting with intermediate-risk disease, remains a topic of dialogue among clinicians. Given this area of uncertainty, the Research Excellence, Active Leadership (REAL) Canadian Breast Cancer Alliance conducted a modified Delphi process to assess the level of agreement among Canadian expert clinicians on various staging recommendations. In total, 20 items were drafted covering staging based on biological status, the utilization of localization clips, both for the axilla during diagnosis and primary surgical site for margins and radiation therapy planning, and the use of advanced imaging for the investigation of distant metastases. Overall, the consensus threshold among all participants (i.e., ≥75% agreement) was reached in 20/20 items. Differences in clinical practice and recent findings from the literature are provided in the discussion. These consensus recommendations are meant to help standardize breast cancer staging practices in Canada, ensuring accurate diagnosis and optimal treatment planning.